SYMPTOMATIC THERAPY FOR PAIN IN RHEUMATIC DISEASES: A PLACE OF ACECLOFENAC - V A Nasonova; Andrei Evgenyevich Karateev (Современная ревматология)
Nonsteroidal anti-inflammatory drugs (NSAID) are prominent among the analgesics used in rheumatology. The effects of aceclofenac are described in rheumatic diseases. It is noted that it is an available effective NSAID, which is distinguished for its balanced analgesic and anti-inflammatory activities and a good tolerability and may be recommended for both rapid analgesia in urgent situations and long-term treatment of pain in chronic diseases.